2023
DOI: 10.21608/mid.2023.193210.1466
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare facilities’ level of preparedness response on COVID-19 preventive measures in selected regions of Tanzania: A perspective of healthcare workers

Abstract: Background: After the first patient of COVID-19 was announced by the Ministry of Health in Tanzania from Arusha region, the hottest discussion in the community was the fear on how our health facilities were prepared against the spread of coronavirus disease. Objective and significance: This study aims at assessing healthcare facilities level of preparedness response on preventive measures against COVID-19 in selected regions of Tanzania through the contributions of healthcare workers. This study will add value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Another study conducted in Tanzania strengthened that, overall level of preparedness was poor at 52%, only 25% of preventive measures were good prepared and 23% moderately prepared in which regular training among healthcare workers was poorly implemented, then concluded that poor preparedness responses in Tanzania may cause less capacity to fight against COVID-19 whenever it emerges. 23 Therefore, the results shows a direct relationship between poor preparedness responses and moderate knowledge reported by this current study.…”
Section: Discussionsupporting
confidence: 52%
“…Another study conducted in Tanzania strengthened that, overall level of preparedness was poor at 52%, only 25% of preventive measures were good prepared and 23% moderately prepared in which regular training among healthcare workers was poorly implemented, then concluded that poor preparedness responses in Tanzania may cause less capacity to fight against COVID-19 whenever it emerges. 23 Therefore, the results shows a direct relationship between poor preparedness responses and moderate knowledge reported by this current study.…”
Section: Discussionsupporting
confidence: 52%
“…(19) En la actualidad no es fácil luchar contra el COVID-19 de manera eficaz y eficiente si la enfermedad continúa apareciendo, pues la situación podría empeorar las instalaciones sanitarias debido a sistemas de salud que no son capaces de dar respuestas preparadas, y que en este momento son bastante limitadas; esto porque muchas de las medidas implementadas fueron suspendidas al menguar la crisis originada por la pandemia. (36) En función de la revisión realizada se recomienda que las normas de bioseguridad que fueron aplicadas en el pasado sean mejoradas y actualizadas, brindando una formación constante a la totalidad del personal, en especial a las enfermeras, pues son quienes brindan el apoyo necesario tanto a médicos como a pacientes.…”
Section: Discussionunclassified